Strategi Mitigasi Kebakaran Lahan Terhadap Kualitas Udara dan Risiko Kesehatan Masyarakat (Studi Kasus: Kecamatan Pangkalan Kerinci, Kabupaten Pelalawan, Provinsi Riau) - Indra Hartanto; Sukendi Sukendi; Tengku Nurhidayah (Pelantar Press, 2023)
Land fires are occurred almost every year during the dry season in Pangkalan Kerinci District. These condition resulted in damage and loss in terms of economic, social and environment that will inhibit the rate of development in Pangkalan Kerinci District so that necessary control measures against land and forest fires. The research method used was a case study, the samples for this study were selected through purposive sampling method were the data for this study were obtained through questioner, interview and observation. The results of this study that there are influence between the incidence of land fires with the level of air quality and the level of public health that occurs in Pangkalan Kerinci District, the formulation of a mitigation strategy for preventing land fires in Pangkalan Kerinci District in quadrant 1, which means that the land fire mitigation strategy must carry out a progressive strategy by utilizing internal; strengths to take advantage of external opportunities to achieve the optimal strategy.